The Effects of L1 English Constraints on the Acquisition of the L2 Spanish Alveopalatal Nasal - Stefanich, Sara; Cabrelli, Jennifer (Frontiers in Psychology, 2021)
This study examines whether L1 English/L2 Spanish learners at different proficiency levels acquire a novel L2 phoneme, the Spanish palatal nasal /ɲ/. While alveolar /n/ is part of the Spanish and English inventories, /ɲ/, which consists of a tautosyllabic palatal nasal+glide element, is not. This crosslinguistic disparity presents potential difficulty for L1 English speakers due to L1 segmental and phonotactic constraints; the closest English approximation is the heterosyllabic sequence /nj/ (e.g., ‘canyon’ /kænjn̩/ [ˈkhæn.jn̩], cf. Spanish cañón ‘canyon’ /kaɲon/ [ka.ˈɲon]). With these crosslinguistic differences in mind, we ask: 1a) Do L1 English learners of L2 Spanish produce acoustically distinct Spanish /n/ and /ɲ/ and 1b) Does the distinction of /n/ and /ɲ/ vary by proficiency? In the case that learners distinguish /n/ and /ɲ/, the second question investigates the acoustic quality of /ɲ/ to determine 2a) if learners’ L2 representation patterns with that of an L1 Spanish representation or if learners rely on an L1 representation (here, English /nj/) and 2b) if the acoustic quality of L2 Spanish /ɲ/ varies as a function of proficiency. Beginner (n=9) and advanced (n=8) L1 English/L2 Spanish speakers and a comparison group of 10 L1 Spanish/L2 English speakers completed delayed repetition tasks in which disyllabic nonce words were produced in a carrier phrase. English critical items contained an intervocalic heterosyllabic /nj/ sequence (e.g. [ˈphɑn.jə]); Spanish critical items consisted of items with either intervocalic onset /ɲ/ (e.g. [ˈxa.ɲa]) or /n/ [ˈxa.na]. We measured duration and formant contours of the following vocalic portion as acoustic indices of the /n//ɲ/ and /ɲ/ /nj/ distinctions. Results show that, while L2 Spanish learners produce an acoustically distinct /n/ /ɲ/ contrast even at a low level of proficiency, the beginners produce an intermediate /ɲ/ that falls acoustically between their English /nj/ and the L1 Spanish /ɲ/ while the advanced learners’ Spanish /ɲ/ and English /nj/ appear to be in the process of equivalence classification. We discuss these outcomes as they relate to the robustness of L1 phonological constraints in late L2 acquisition coupled with the role of perceptual cues, functional load, and questions of intelligibility.